Managing and Responding to FDA Inspections - Muhr Leister, Susan Margaret (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Is your facility inspection ready at all times? Most organization are not ready at all times and, therefore find preparing for any type of FDA Inspection to be overwhelming. This paper provides guidance on how to prepare and how to respond to the FDA, specifically for larger clinical site inspections, Clinical Investigators, and drug manufacturer inspections. Also, tips are provided on how to take a proactive inspection readiness approach. These same inspection readiness strategies can be applied in a reduced manner by smaller organizations to help successfully manage regulatory inspections.
Keywords: regulatory inspections